2017
DOI: 10.1037/ccp0000187
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a web-based, personalized normative feedback alcohol intervention for young-adult veterans.

Abstract: Objective Young adult American veterans are at-risk for problematic alcohol use. However, they are unlikely to seek care and may drop out from lengthy multicomponent treatments when they do get care. This randomized controlled trial tested a very brief alcohol intervention delivered over the Internet to reach the population of young adult veterans to help reduce their drinking. Method Veterans (N=784) were recruited from Facebook and randomized to either a control condition or a personalized normative feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 81 publications
2
75
0
Order By: Relevance
“…Participants were young adults aged 18 to 34 years who were recruited using targeted Facebook ads as part of a larger randomized controlled trial (Pedersen, Parast, Marshall, Schell, & Neighbors, 2017). Eligibility criteria included (a) being a U.S. veteran currently separated from active duty, (b) being between ages 18 to 34 years, and (c) scoring 3/4+ (for women/men) on the Alcohol Use Disorders Identification Test (Saunders, Aasland, Babor, de la Fuente, & Grant, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were young adults aged 18 to 34 years who were recruited using targeted Facebook ads as part of a larger randomized controlled trial (Pedersen, Parast, Marshall, Schell, & Neighbors, 2017). Eligibility criteria included (a) being a U.S. veteran currently separated from active duty, (b) being between ages 18 to 34 years, and (c) scoring 3/4+ (for women/men) on the Alcohol Use Disorders Identification Test (Saunders, Aasland, Babor, de la Fuente, & Grant, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 622 participants (79% follow-up rate) completed the one-month follow-up survey online and were included in analyses for this study. Details regarding recruitment procedures, sample characteristics, and intervention outcomes have been published elsewhere (Pedersen, Naranjo, & Marshall, 2017; Pedersen, Parast, et al, 2017). All procedures were approved by the institutional review board.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Facebook ads have been used effectively in populations including college students and young adults [16,17] and military veterans (particularly those with risky drinking) [18][19][20][21]. Prior research has also suggested ad campaigns can achieve both "broad reach and targeted recruitment," and found ad costs to be manageable [19].…”
Section: Introductionmentioning
confidence: 99%